Development of a rapid LC-MS/MS method for the simultaneous quantification of various flavonoids, isoflavonoids, and phytohormones extracted from Medicago truncatula leaves. Issue 15 (2nd October 2021) - Bisht, Neema; Gupta, Arunima; Awasthi, Pallavi; Goel, Atul; Chandran, Divya; Sharma, Neha; Singh, Nirpendra
Abstract: Flavonoids, isoflavonoids, and phytohormones are small metabolites of plants, which are involved in the regulation of plant development and/or defense against pathogens. Quantitation of these metabolites in plants is important to basic research on crop protection and in the food and herbal industry. Hence, a robust, reliable, and sensitive method is required for the analysis of these compounds in plant samples. In the present study, a high-performance liquid chromatographic-tandem mass spectrometric (HPLC–ESI-MS/MS) method was developed and validated for the determination of isoflavonoids including genistein, daidzein, formononetin, biochanin A, 2′-hydroxyformononetin, 2′-methoxyformononetin, medicarpin, flavonoids; liquiritigenin, naringenin, and phytohormones; salicylic acid and jasmonic acid in Medicago truncatula . The analytes were separated by means of C-18, reversed-phase chromatography, and detected using QTRAP mass spectrometer. The on-column limit of detection of all the analytes was as low as 0.03 pg, whereas the limit of quantification of all the compounds was observed up to 0.1 pg levels. Further the method was also validated in terms of selectivity, linearity ( r 2 > 0.99), recovery (90.6–110.3%), accuracy (RE% ≤ 3%) and precision (RSD% ≤ 3%). As a proof of concept, the developed method was successfully used for the quantitation of these metabolites from leaf extract of M. truncatula . Graphical Abstract: UF0001